Metformin therapy in pediatric type 2 diabetes mellitus and its comorbidities: A review - Alfaraidi, Haifa; Samaan, M. Constantine (Frontiers in Endocrinology, 2023)
Type 2 diabetes (T2D) rates in children and adolescents are rising globally. T2D is a complex and aggressive disease in children with several comorbidities, high treatment failure rates, and insulin needs within a few years of diagnosis. While myriads of pharmacotherapies are licensed to treat adults with T2D, treatments accessible to children and adolescents have been limited until recently. Metformin is an old drug with multiple beneficial metabolic health effects beyond glycemic effects. This review discusses Metformin's origins, its mechanisms of action in multiple organs, and evidence for its use in the pediatric population to treat and prevent T2D. We also explore the evidence for its use as an obesity therapy, which is the primary driver of T2D, and T2D-driven comorbidities. While emerging therapies create new horizons for managing pediatric T2D, Metformin remains an inexpensive and safe part of the treatment plans of many T2D children for its beneficial metabolic effects.